2000
DOI: 10.1046/j.1365-2036.2000.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection is associated with milder gastro‐oesophageal reflux disease

Abstract: Background: We have previously demonstrated a negative relationship between the prevalence of Helicobacter pylori and gastro‐oesophageal reflux disease (GERD). Aim: To study the effects of H. pylori infection on the severity of GERD. Methods: Ethnic Chinese patients with frequent heartburn and/or endoscopic oesophagitis were studied. Endoscopic examination was performed to assess the severity of oesophagitis (modified Savary–Miller grading) and the presence of hiatus hernia. Biopsies were taken for rapid ureas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
2
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 22 publications
7
71
2
5
Order By: Relevance
“…In our study, we observed neither a change in the gastrin level nor in GERD occurrence between H. pylori-infected and non-infected state. In contrast to these hypotheses, we could not demonstrate any relationship between gastrin and GERD, which was comparable with a few studies in the literature (18)(19)(20)(21)(22)(23)(24). One of the reasons for this difference can be the predominant corpoantral infection in our patients.…”
Section: Discussioncontrasting
confidence: 56%
“…In our study, we observed neither a change in the gastrin level nor in GERD occurrence between H. pylori-infected and non-infected state. In contrast to these hypotheses, we could not demonstrate any relationship between gastrin and GERD, which was comparable with a few studies in the literature (18)(19)(20)(21)(22)(23)(24). One of the reasons for this difference can be the predominant corpoantral infection in our patients.…”
Section: Discussioncontrasting
confidence: 56%
“…32 However, our finding is consistent with a subsequent trial of H. pylori positive patients from this cohort, where eradication reduced overall dyspepsia scores (measured by the LDQ), but not reflux scores (measured by the CDRQ) and consequently, reflux was more likely to be the residual predominant symptom. 8 Helicobacter pylori negative patients may have worse oesophagitis than those who are H. pylori positive 33,34 and this may be especially important in relation to cagA status. 35 This study was unable to capture H. pylori strain as this is not a routinely available laboratory test.…”
Section: Discussionmentioning
confidence: 99%
“…13 The presence of chronic active H. pylori gastritis has been shown to be associated with milder forms of reflux disease and eradication therapy in patients with corpus-predominant gastritis increases the risk of developing GERD in patients with ulcer disease. 2,14 There is little information on the pattern of gastritis in Caucasian subjects with dyspepsia and on the development of GERD after H. pylori eradication in non-ulcer dyspepsia. The aim of our study was to determine the incidence of GERD in patients with documented non-ulcer dyspepsia who received eradication therapy and were followed-up for 1 year.…”
Section: Introductionmentioning
confidence: 99%